Evaluation of a 'serious game' on nursing student knowledge and uptake of influenza vaccination. - Gary Mitchell; Laurence Leonard; Gillian Carter; Olinda Santin; Christine Brown Wilson (PLoS ONE)
Background Influenza is a serious global healthcare issue that is associated with between 290,000 to 650,000 deaths annually. The aim of this study is to evaluate the effect of a 'serious game' about influenza, on nursing student attitude, knowledge and uptake of the influenza vaccination. Methods 1306 undergraduate nursing students were invited, via email, to play an online game about influenza between September 2018 and March 2019. 430 nursing students accessed the game and completed an 8-item questionnaire measuring their attitudes to influenza between September 2018 and March 2019. In April 2019, 356 nursing students from this sample completed a follow-up 2-item questionnaire about their uptake of the influenza vaccination. A larger separate 40-item knowledge questionnaire was completed by a year one cohort of 124 nursing students in August 2018 prior to receiving access to the game and then after access to the game had ended, in April 2019. This sample was selected to determine the extent to which the game improved knowledge about influenza amongst a homogenous group. Results In the year preceding this study, 36.7% of the sample received an influenza vaccination. This increased to 47.8% after accessing to the game. Nursing students reported perceived improvements in their knowledge, intention to get the vaccination and intention to recommend the vaccination to their patients after playing the game. Nursing students who completed the 40-item pre- and post-knowledge questionnaire scored an average of 68.6% before receiving access to the game and 85.2% after. Using Paired T-Tests statistical analysis, it was determined that this 16.6% increase was highly statistically significant (P < 0.001). Conclusions The research highlights that the influenza game can improve knowledge and intention to become vaccinated. This study suggests that improvement in influenza knowledge is likely to encourage more nursing students to receive the influenza vaccination.